ECONOMIC PERFORMANCE IN POST-SOVIET AND POST-COMMUNIST COUNTRIES – EVIDENCE FROM PANEL DATA AND MULTIVARIATE STATISTICAL ANALYSIS (The South East European Journal of Economics and Business, 2021)
The study examines the impact of a set of determinants of economic growth, which are widely emphasised in the literature, in a group of 27 selected post-Soviet, post-communist and transition countries from Central and Eastern Europe, the former Soviet Union, and Mongolia during 1997–2017. The set of baseline variables includes, among others, trade openness, investment rate, public consumption spending, and selected demographic factors. The methodology uses panel data and it is supported by multivariate statistical methods of grouping objects. The panel data used provides results that are mainly consistent with the literature review. However, the effects of demographic factors are rather not significant, but the role of investment has been emphasised. In turn, the multivariate statistical approaches indicate the shifts in regional de(similarity) between the analysed countries with respect to the performance of the selected variables over the last 20 years.